Levoketoconazole treatment in endogenous Cushing's syndrome: extended evaluation of clinical, biochemical, and radiologic outcomes - Fleseriu, Maria; Auchus, Richard J.; Greenman, Yona; Zacharieva, Sabina; Geer, Eliza B.; Salvatori, Roberto; Pivonello, Rosario; Feldt-Rasmussen, Ulla; Kennedy, Laurence; Buchfelder, Michael; Biller, Beverly Mk; Cohen, Fredric; et al. (European Journal of Endocrinology, 2022)
Objective: This extended evaluation (EE) of the SONICS study assessed the effects of levoketoconazole for an additional 6 months following open-label, 6-month maintenance treatment in endogenous Cushing's syndrome. Design/Methods: SONICS included dose-titration (150-600 mg BID), 6-month maintenance, and 6-month EE phases. Exploratory efficacy assessments were performed at months 9 and 12 (relative to the start of maintenance). For pituitary MRI in patients with Cushing's disease, a threshold of ≥2 mm denoted change from baseline in the largest tumor diameter. Results: Sixty patients entered EE at month 6; 61% (33/54 with data) exhibited normal mean urinary free cortisol (mUFC). At months 9 and 12, respectively, 55% (27/49) and 41% (18/44) of patients with data had normal mUFC. Mean fasting glucose, total and LDL-cholesterol, body weight, BMI, abdominal girth, hirsutism, CushingQoL, and Beck Depression Inventory-II scores improved from the study baseline at months 9 and 12. Forty-six patients completed month 12; four (6.7%) discontinued during EE due to adverse events. The most common adverse events in EE were arthralgia, headache, hypokalemia, and QT prolongation (6.7% each). No patient experienced alanine aminotransferase or aspartate aminotransferase >3× upper limit of normal, Fridericia-corrected QT interval >460 ms, or adrenal insufficiency during EE. Of 31 patients with tumor measurements at baseline and month 12 or follow-up, the largest tumor diameter was stable in 27 (87%) patients, decreased in one, and increased in three (largest increase 4 mm). Conclusion: In the first long-term levoketoconazole study, continued treatment through a 12-month maintenance period sustained the early clinical and biochemical benefits in most patients completing EE, without new adverse effects.
CRIS-Team Scopus Importer:2022-12-16